For the beauty of the church : casting a vision for the arts (Grand Rapids, Mich. : Baker Books, 2010)
In many churches today the arts are an afterthought at best and forbidden at worst. This insightful book takes you beyond "how we've always done it," beyond fads, beyond mere imitation of the culture, and beyond utilitarianism to develop a robust, dynamic, and substantive vision for the place of the arts--and artists--in our churches. --from publisher description.
Introduction -- The Gospel : how is art a gift, a calling, and an obedience? / Andy Crouch -- The worship : how can art serve of the corporate worship of the church? / John D. Witvliet -- The art patron : someone who can't draw a straight line tries to defend her art-buying habit / Lauren F. Winner -- The pastor : how artists shape pastoral identity / Eugene Peterson -- The artist : what exactly is an artist, and how do we shepherd them? / Barbara Nicolosi -- The practitioner : nurturing artists in the local church / Joshua Banner -- The dangers : what are the dangers of artmaking in the church? / W. David O. Taylor -- The future : looking to the future : a hopeful subversion / Jeremy Begbie.
Includes bibliographical references (p. 193-199).
Keywords: Christianity and the arts; Art and religion